Altered microbiota of the lower respiratory tract and its association with COVID-19 severity analysed by metagenomics and metatranscriptomics - Denian Wang; Yishang Duan; Lijuan He; Juan Jiang; Jinghong Xian; Ke Yuan; Rui Zhang; Huohuo Zhang; Jing Wang; Nan Li; Min Huang; Chenggong Hu; et al. (Communications Biology)
Abstract The interaction between gut and oropharyngeal microbiota plays a significant role in the viral infections like SARS-CoV-2, but role of the lower respiratory tract microbiota remains unclear. Our study utilized metatranscriptomics and metagenomics to analyze the microbial composition of bronchoalveolar lavage fluid and sputum samples from 116 COVID-19 patients, categorized into mild, severe, and critical groups. Our analysis revealed significant differences in viral genotypes across disease stages. As disease severity increased, the Chao index also rose. The mild group was predominantly dominated by Firmicutes, while the severe group showed an increase in Bacteroidetes. The critical group was characterized by a higher abundance of Actinobacteria and Proteobacteria. Notably, the abundance of Streptococcus and Rothia decreased as the disease progressed. Additionally, the Shannon index correlated with mortality risk, while the Chao index was associated with ICU admission, mechanical ventilation, and patient survival. These findings highlight the strong link between microbial composition and COVID-19 severity, providing valuable insights for assessing disease progression.